TINGKAT PEMAHAMAN GURU PJOK TERHADAP KURIKULUM MERDEKA BELAJAR DI SMP SEKECAMATAN KALINYAMATAN JEPARA - Khoirun Nisa', Fitrianti; Slamet Pratama, Dani; Wiyanto, Agus (Journal of Physical Activity and Sports (JPAS), 2024)
Fitrianti Khoirun Nisa' "PJOK Teachers' Level of Understanding of the Independent Learning Curriculum in Middle Schools in the Kalinyamatan Jepara District". Supporting aspects of PJOK teachers' readiness to accept curriculum changes are teacher handbooks, teacher handbooks for students, related learning equipment and media, and existing school infrastructure. This research aims to determine PJOK teachers' understanding of KMB. This research uses a descriptive qualitative approach. This data collection was carried out using observation, interviews, and documentation. The data source for this research was obtained from PJOK SMP teachers. This research data analysis uses data collection, data reduction, data presentation, and concluding. The results that have been obtained by the author who has conducted research are that teachers have a fairly good understanding of prioritizing freedom in more innovative and responsive learning. Most teachers implement learning to encourage student creativity that suits students' interests and talents. However, teachers have several obstacles, one of which is facilities and infrastructure. The school continues to strive to support the existence of an independent learning curriculum.